Pelatihan dan Pendampingan Penyusunan Laporan Keuangan dengan Sistem Data Keuangan Cilacap (SIKECIL) sebagai Upaya Peningkatan Kualitas Koperasi AGRO IHWANI Bolang - Mulyani, Eva; Prabawati, Mega Nur; Yulianto, Eko; Nurhayati, Elis; Apiati, Vepi (LSM Catimore dan Sahabat, 2024)
Cooperatives play an important role in the community economy, especially in supporting the growth of the small and medium business sector. However, one of the main challenges faced by cooperatives is the low quality of financial reports, which has an impact on transparency and accountability in financial management. To overcome this problem, training and mentoring activities for the preparation of financial reports with the Cilacap Financial Data System (SIKECIL) have been carried out at the AGRO IHWANI Bolang Cooperative, Cilacap Regency. This training aims to improve the capacity of cooperative administrators in preparing accurate financial reports, in accordance with accounting standards, and effectively and efficiently. The Cilacap Financial Data System (SIKECIL) is a dynamic application using a spreadsheet designed to facilitate the input of various types of accounting transactions by users in one step, with the ultimate goal of producing comprehensive cooperative financial reports. In making SIKECIL, a unique programming language is used which is intended for cooperative financial management. The methods used include the PRA (Participatory Rural Appraisal) approach, FGD (Focus Group Discussion), as well as counseling and training. The results of this activity show an increase in the understanding and skills of administrators in preparing financial reports using the better SIKECIL application, as well as an increase in the quality of transparency and accountability in cooperative financial management.